ANALISIS MATERI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH - Thoyibah, Firda Amalia (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
This research is motivated by the importance of understanding the History of Islamic Culture (SKI) in Madrasahs as an integral part of Islamic religious education in Indonesia. The purpose of this study is to analyze the learning materials of SKI, identify effective approaches, and evaluate the challenges faced in teaching. The method used is a literature review, which collects and analyzes various literatures related to SKI teaching. The results show that the application of methods such as Contextual Teaching and Learning and the use of e-learning technology can increase student engagement in learning. In addition, there are challenges in the suitability of materials with the curriculum and limited resources that need to be overcome, teaching SKI does not only function as a delivery of historical information, but also plays a role in shaping students' Islamic character and identity. The implications of this study emphasize the need for relevant curriculum development and training for teachers, so that SKI learning is more effective and able to answer the needs of students in the modern era. With the right approach, it is hoped that SKI learning can contribute to building a generation that understands and lives Islamic values in their historical context.